State of the nation: class, Labour politics and the contemporary relevance of Our Friends in the North (1996) - Collins, Jeremy (Intellect, 2023)
In January 1996 the BBC began broadcasting Our Friends in the North, a ‘state of the nation’ drama (Eaton 2005), over nine episodes. The series followed four working-class friends from Tyneside, and explored how their lives unfolded during the social and political upheavals of the 1960s through to the 1990s. The ‘monumental’ series was described at the time as ‘one of the major television programmes of this or any other year’. A recent (September 2022) rescreening of the series has re-emphasized the relevance of the themes it explores, and a one-off radio play updated the story to follow the children of the original characters in the 2020s. The series has been situated in the canons of British social realism and quality drama, and explores issues of class and social power, in particular depicting struggles around poor housing, police corruption, political scandals, and how these intersect with the lives of ordinary people. The main characters are shown variously rejecting, accommodating to or being crushed by, the political changes of the period, from Wilsonian Labourism, via Thatcherite neo-liberalism to the emergence of ‘new labour’. This article juxtaposes examples of the series’ themes with contemporary news items (around housing, political corruption, an out-of-control Metropolitan police service and a timid, subservient, managerial Labour Party). It argues that these recent, unresolved developments in the United Kingdom suggest the continued salience of Our Friends in the North as an important commentary on social and political issues.